Perbandingan Teori Belajar Sosial dan Siksa Kubur (Perspektif Ulama Malaysia dan Cendekiawan Barat) - Halimatus Sa’diah; Laila Musrifah Sofiyanti; Sulaiman; Luqman Baehaqi; Abdul Syahid (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2025)
The torment of the grave is a consequence that must be accepted and seems to be a punishment for a servant as a form of retribution for every behavior he has done during his life in the world. The similarity of the context related to the torment of the grave between Tuan Minal's perspective and Albert Bandura's social learning theory has a gap of difference which is the basis for this research so that the author conducted a comparative analysis from the perspective of both figures. The purpose of writing this article is to find the differences and similarities in the concept of reinforcement from a comparative analysis of Tuan Minal's thoughts on the torment of the grave with Albert Bandura's thoughts. This study uses a qualitative research method with a comparative analysis technique. The results of the study show that Ibn Qayyim al-Jauziyah's thoughts on the torment of the grave have a similar concept in Albert Bandura's social learning theory, namely the torment of the grave as a form of reinforcement so that individuals do not repeat bad behavior. The difference lies in the aspects of the form of reinforcement, the form of change, the time of administration, behavioral patterns, the function of observation in modeling, model classification, and the success of reinforcement Keywords: Torture of the Grave; Tuan Minal; Albert Bandura.